A study on the factors that lead to work stress among HR practitioners in Malaysia Marine and Heavy Engineering (MMHE), Pasir Gudang / Noor Haiyu Nasri and Nurul Nadiah Mohd Nor - Nasri, Noor Haiyu; Mohd Nor, Nurul Nadiah (Faculty of Business and Management, 2013)
Work stress is not a new issue. However, in recent years it has become more apparent. Nowadays, work stress also will be the main reasons why an employee leaves their company even though the company is a huge and have a good company’s reputation. It also will affect employees mental and physical health as well as the organization performance. Besides that, there have been frequent complaints from employees of Malaysia Marine and Heavy Engineering (MMHE), Pasir Gudang that they have a very heavy workload. In this research study, only three influence factors that lead to work stress among the HR Practitioners in the company which are workload, role conflict and interpersonal relationship at work. Moreover, data is collected by distributing questionnaire to 40 respondents from HR Division by using probability sampling which is simple random sampling. Nevertheless, majority of the respondents age are between 25 to 35 years old with non-executive level of position.In this research, regression backward analysis method is used in order to identify which factor is most significant to work stress among HR Practitioners in Malaysia Marine and Heavy Engineering (MMHE), Pasir Gudang. This research study also said to be beneficial to the company as the employees are currently facing work stress. It will help the employees to manage their emotion from getting worse. Recommendations for future research are also been discussed.